Diseño del sistema de fuerza de laboratorio de telecomunicaciones y sistemas operativos de la carrera de ingeniería en sistemas UNL. - Loján Cisneros, Cristian Byron (2014)
The current technical report details the procedure performed and design facilities for electric power system, telecommunications laboratory and operating systems, which were implemented in the area of Energy Industries and Non Renewable Natural Resources of the National University of Loja. Here you can find some important concepts and descriptions of materials that are usually used in an installation of computer laboratories, work may also contribute to other laboratories that could be deployed inside or outside the University. The design was made by performing such calculations; an example of this is; to determine the thermomagnetic protection to maintain good safety with in the laboratory. An investigation of all materials that will be needed to bring the lab with their respective electrical power installations was conducted once analyzed and researched it proceeded to make the budget and all these respective procedure. Thanks to this work, we can attach a classroom as a laboratory for telecommunications and operating systems for the students of engineering degree in systems, so they can develop their skills in practice.